A Chinese patient with the clinical features of Parkinson's disease contains a single copy of octarepeat deletion in PRNP case report. Issue 1 (1st January 2021) - Shi, Qi; Shen, Xiao-Jing; Gao, Li-Ping; Xiao, Kang; Zhou, Wei; Wang, Yuan; Chen, Cao; Dong, Xiao-Ping
ABSTRACT: Insertion or deletion of single copy of octapeptide repeat (OR) in human PrP protein are considered as polymorphism, while of insertions of more numbers of OR and deletion of two copies of OR are associated with genetic prion diseases. Here, we reported a 58-year-old female patient who displayed clinical manifestations of Parkinson's disease (PD) but contained deletion mutation of single copy of OR in one PRNP allele. The patient complained involuntary tremor of left upper limb for 18 months and her symptoms aggravation for 6 months at the time referring to Chinese National CJD surveillance system. The tremor was pronounced at rest, exacerbated by stress and disappear during sleep. Her symptoms were partially relieved after receiving medicament for PD. Neurological examination recorded involuntary movement of left hand and gear-like muscle tension of left upper limb. Coordination movement reported positive of Romberg sign and unstable in heel-keen test. EEG recorded a mild abnormality, but without periodic sharp wave complexes (PSWC). MRI showed a mild write matter demyelination. CSF protein 14-3-3 was negative. PRNP sequencing revealed heterozygosity of single copy deletion on ORs (R1-2-3-4/R1-2-2-3-4). No family history of neurodegenerative disease was recorded. Such case with a single copy of OR deletion in PRNP displaying the feature of PD is rarely reported in Chinese mainland.